Managing the accountability–autonomy tensions in university research commercialisation. (14th August 2017) - Narayan, Anil K.; Northcott, Deryl; Parker, Lee D.
Abstract: This article investigates organisational responses to emerging concerns about how accountability–autonomy tensions can be managed within the context of university research commercialisation. The findings suggest that changed expectations of university research practices, which result from the introduction of a commercialisation logic, can be managed via the homogenisation of research goals and strategies. The successful management of accountability–autonomy tensions also depends on utilising the various structures and cultural contexts that can be facilitated by decoupling and bridging strategies. Further, while adopting symbolic systems may enhance legitimacy, failure to implement material practices and provide the appropriate cultural context to manage conflicting relationships may put university commercialisation ambitions at risk.